Design and Implementation of Network Monitoring System on Local Area Network with Social Media Twitter Notification - Winasis, Bima Putra; Sugiantoro, Bambang (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
A network administrator has responsibility and important role in a computer network. Network security and its services depend on the treatment performed by the administrator. Network administrators who understand the workings of a computer network is needed to obtain the necessary computer networks. One of the obligations of the administrator is to monitor a network which can be done by using the system monitor. Monitoring system is a task to check the computer, operating system and services of computer network to keep the network always work in optimal conditions. In an effort to monitor the condition of the network, one of the technologies that can be used is the notification on twitter social media for providing information in real time to the administrator. Twitter is a social media that is very widely used, free, and secure. Moreover, the use of social media twitter experiencing rapid development. Therefore, the selection of twitter as a medium for the use of the notification is expected to be the right strategy. This system will be made by sending notification via twitter when a LAN network is disconnected or attacked by intruders.Results from the development of systems that have been made based on testing the functionality of the system shows all functions of the system has been running well. While usability testing calculation of the total score of the test system interface to get a score of 38.75 out of a maximum scale of 50. This score is in the range 34-42 value (Satisfied) which means that the respondents were satisfied with the system interface. Therefore, this interface is good to be implemented in the system.